Between Empire and Revelation: Hoesein Djajadiningrat and the Politics of Islamic Knowledge in Dutch East Indies - Mohammad Refi Omar Ar Razy (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This article analyzes the intellectual genealogy of Hoesein Djajadiningrat from the perspective of postcolonial theory. This framework has significantly influenced scholarly discussions regarding Islamic politics and jurisprudence in colonial Indonesia. It responds to three main inquiries: First, how did Hoesein interact with Islamic political philosophy? Second, how did he determine the fundamentals of Islamic law? Third, how precisely did he reframe Persian theories of Islamization? Using historical methods like historiography, source criticism, interpretive analysis, and heuristic inquiry, this study analyzes Hoesein's published works and correspondence to provide the first comprehensive analysis of his intellectual growth. This study reveals a portrait of a thinker whose intellectual stance defies simple categorization. Hoesein actively challenged Western ways of thinking while promoting Islamic views deeply influenced by Persian Sufi ideas, local customs, and colonial laws. His works demonstrate both a conformity to and a defiance of the prevailing Orientalist frameworks. Rather than viewing Hoesein as merely a colonial mediator or nationalist critic, this study portrays him as a perceptive interpreter who skillfully navigated the overlapping influences of imperial power and local cultural expressions. His scholarly contributions are crucial to understanding the dynamics of the production of Islamic knowledge in the Dutch East Indies, particularly the conflicts and intersections between regional epistemic traditions and global Islamic thought.